Preparation of Some Culture Media Locally from leaves and stems of Purslane plant (Portulaca oleracea oleracea L.) and Assessment of Their Efficiency Comparing with Culture Media of Oxoid Company (Baghdad Science Journal, 2015)
The leaves and stems of the local Purslane plant ( Portulaca oleracea oleracea L. ) were used to preapare the extract of two types ( wet and dried extractions) the extracts were prepared by weighting of 60grams of the wet and the dried plant individually, then boiled in 500ml of distal water. Finally the volume was completed to1 liter, then we used these extracts to prepare of 8 types of the culture media contained basic, selective and enrichment media for growing a group of pathogenic bacteria. 8 types of bacteria were used for this purpose: Escherichia coli, Pseudomonas flouresence, Staphylococcus aureus , Staphylococcus epidermidis, Bacillus subtilis , Klebsiella pneumoniae , Proteus mirabilis and Proteus vulgaris. The stastical analysis of the results showed that the locally prepared culture media in this research (Nutrient wet portulaca agar , Blood - wet portulaca agar, Manitol- wet portulaca agar, Lactose- wet portulaca agar, Nutrient dried portulaca agar , Blood - dried portulaca agar , Manitol- dried portulaca agar and Lactose- dried portulaca agar) were suitable for culturing of these pathogenic bacteria when compared to the media that supplied by Oxoid company. In addition they also revealed good growth and they were sufficient to use as basic, enriched and selective media .